2018
DOI: 10.1002/lol2.10063
|View full text |Cite
|
Sign up to set email alerts
|

Increasing dominance of terrigenous organic matter in circumpolar freshwaters due to permafrost thaw

Abstract: Climate change and permafrost thaw are unlocking the vast storage of organic carbon held in northern frozen soils. Here, we evaluated the effects of thawing ice‐rich permafrost on dissolved organic matter (DOM) in freshwaters by optical analysis of 253 ponds across the circumpolar North. For a subset of waters in subarctic Quebec, we also quantified the contribution of terrestrial sources to the DOM pool by stable isotopes. The optical measurements showed a higher proportion of terrestrial carbon and a lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
135
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 69 publications
(100 reference statements)
7
135
3
Order By: Relevance
“…DOC, DON and DIN are metabolized at variable rates (van Hees et al 2005, Harms and Jones 2012, and DOC and DON can sorb to mineral soil Asner 2001, Kawahigashi et al 2006), transform along surface and subsurface flow paths (Striegl et al 2005, Koch et al 2013, or accumulate in pore waters in poorly drained areas (Wickland et al 2007). Nevertheless, studies of permafrost-impacted ecosystems across the circumpolar region have documented changes in DOC and TDN consistent with our conclusion that near-surface permafrost soils can be important DOC and TDN sources upon thaw (Harms et al 2013, Abbott et al 2015, Loiko et al 2017, Keuper et al 2012, Wauthy et al 2018. Regional studies in Siberia and Alaska broadly align with our findings (Frey and Smith 2005, Frey et al 2007, Walvoord and Striegl 2007, although many factors beyond release of soil-derived DOC and TDN are important at these large scales.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…DOC, DON and DIN are metabolized at variable rates (van Hees et al 2005, Harms and Jones 2012, and DOC and DON can sorb to mineral soil Asner 2001, Kawahigashi et al 2006), transform along surface and subsurface flow paths (Striegl et al 2005, Koch et al 2013, or accumulate in pore waters in poorly drained areas (Wickland et al 2007). Nevertheless, studies of permafrost-impacted ecosystems across the circumpolar region have documented changes in DOC and TDN consistent with our conclusion that near-surface permafrost soils can be important DOC and TDN sources upon thaw (Harms et al 2013, Abbott et al 2015, Loiko et al 2017, Keuper et al 2012, Wauthy et al 2018. Regional studies in Siberia and Alaska broadly align with our findings (Frey and Smith 2005, Frey et al 2007, Walvoord and Striegl 2007, although many factors beyond release of soil-derived DOC and TDN are important at these large scales.…”
Section: Discussionsupporting
confidence: 78%
“…Near-surface permafrost soils store substantial C and N stocks (Harden et al 2012, Hugelius et al 2014 that are vulnerable to soluble C and N release upon thaw. Circumpolar studies document differences in DOC and dissolved N concentrations, solute chemical properties, and DOC biodegradability of surface waters draining areas having deep active layers or thermokarst features when compared to areas having shallow stable permafrost (Abbott et al 2014, Harms et al 2013, Wauthy et al 2018. Changing terrestrial sources with thaw are commonly invoked as the cause.…”
Section: Introductionmentioning
confidence: 99%
“…The lifecycle of these ecosystems is expected to be shorter under warmer climate conditions (Vincent et al 2013) and this will in turn expose a higher number of waterbodies to strong lateral influence from the adjacent carbon-rich permafrost erosion that will enrich the lakes and ponds and accordingly stimulate bacterial activity (Vonk et al 2013). In the areas where thawing is ongoing, a shift toward increasing terrestrial dominance of the carbon in freshwaters has already been reported (Wauthy et al 2018).…”
mentioning
confidence: 99%
“…A large share of the carbon in the permafrost is labile and readily available for microbial use (Waldrop et al 2010), making the emerging thaw ponds hotspots for microbial production that may act as an important positive feedback to climate warming. Compared to freshwaters that are less influenced by disappearing permafrost, the molecular composition of the carbon in thaw ponds is characterized by a larger proportion of terrestrially derived dissolved organic matter (DOM) of higher molecular weights combined with a minor influence from compounds derived from autochthonous primary production (Wauthy et al 2018). There is however no information on how DOM quality and the associated microbial composition change throughout the long-term succession of the permafrost thaw ponds.…”
mentioning
confidence: 99%
“…The concentration of DOC in GEC lakes is controlled by the supply of allochtonous organic matter delivered from surrounding areas, peat layers and scattered organic matter in frozen deposits. A trend of increasing organic matter concentration within lake waters has been observed as a result of recent formation of thermocirques .…”
Section: Discussionmentioning
confidence: 99%